Mirroring Solar Radiation Emitting Heat Toward the Universe: Design, Production, and Preliminary Testing of a Metamaterial Based Daytime Passive Radiative Cooler - Anna Castaldo; Giuseppe Vitiello; Emilia Gambale; Michela Lanchi; Manuela Ferrara; Michele Zinzi (Energies, 2020)
A radiative cooling device, based on a metamaterial able to mirror solar radiation and emit heat toward the universe by the transparency window of the atmosphere (8–13 µm), reaching and maintaining temperatures below ambient air, without any electricity input (passive), could have a significant impact on energy consumption of buildings and positive effects on the global warming prevention. A similar device is expected to properly work if exposed to the nocturnal sky, but during the daytime, its efficacy could be affected by its own heating under direct sunlight. In scientific literature, there are only few evidences of lab scale devices, acting as passive radiative cooling at daytime, and remaining few degrees below ambient air. This work describes the proof of concept of a daytime passive radiative cooler, entirely developed in ENEA labs, capable to reach well 12 °C under ambient temperature. In particular, the prototypal device is an acrylic box case, filled with noble gas, whose top face is a metamaterial deposited on a metal substrate covered with a transparent polymeric film. The metamaterial here tested, obtained by means of a semi-empirical approach, is a spectrally selective coating based on low cost materials, deposited as thin films by sputtering on the metallic substrate, that emits selectively in the 8–13 µm region, reflecting elsewhere UV_VIS_NIR_IR electromagnetic radiation. The prototype during the daytime sky could reach temperatures well beyond ambient temperature. However, the proof of concept experiment performed in a bright clear June day has evidenced some limitations. A critical analysis of the obtained experimental results has done, in order to individuate design revisions for the device and to identify future metamaterial improvements.